The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1063/1.2209714
|View full text |Cite
|
Sign up to set email alerts
|

Growth mode and structural characterization of GaSb on Si (001) substrate: A transmission electron microscopy study

Abstract: Growth mode and structural properties of GaSb layers grown on silicon substrate by molecular beam epitaxy method are investigated by transmission electron microscopy. It is found that the GaSb grows to three-dimensional islands and grains are tilted to reduce a lattice mismatch through twin boundaries when they are directly grown on Si substrate. A low-temperature (LT) AlSb buffer plays a key role in transferring the growth mode from a three-dimensional island to a layer-by-layer structure. When the LT AlSb la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
44
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…The IMF arrays have been reported in several systems including GaP/Si [9], GaAs/Si [10], InAs/GaAs [11], InAs/ GaP [12], GaSb/GaAs [14][15][16][17][18], InP/GaAs [21] and AlSb/Si [22,23] over a range of lattice-mismatched conditions ranging from Da o /a o ¼ 0.4% (GaP/Si) to Da o /a o $13% (AlSb/Si). To date, the IMF formation process has not been well established in the literature.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The IMF arrays have been reported in several systems including GaP/Si [9], GaAs/Si [10], InAs/GaAs [11], InAs/ GaP [12], GaSb/GaAs [14][15][16][17][18], InP/GaAs [21] and AlSb/Si [22,23] over a range of lattice-mismatched conditions ranging from Da o /a o ¼ 0.4% (GaP/Si) to Da o /a o $13% (AlSb/Si). To date, the IMF formation process has not been well established in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The latter approach involving IMF formation appears fundamentally different from the metamorphic approach as strain energy is immediately relieved at the interface by laterally propagating (901) misfit dislocations confined to the epi-substrate interface [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. After IMF array formation, subsequent material deposition proceeds in a strainfree layer-by-layer growth mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then the IMF has been implemented in several systems including GaP/Si [11], GaAs/Si [12], InAs/GaAs [13], InAs/GaP [14], InP/GaAs [15], AlSb/Si [16] and GaAs on GaSb [17]. However, so far this mode has not been well-established due to both unrepeatable growth under technological conditions in a narrow epitaxial window and complex characterization.…”
Section: Introductionmentioning
confidence: 99%
“…For the past few years, epitaxial growth and characterization of GaSb layers on Si have been reported by several workers [6][7][8]. Akahane et al [9][10][11] reported the heteroepitaxial growth of GaSb films on Si substrates by introducing an AlSb initiation layer.…”
Section: Introductionmentioning
confidence: 99%